2022
DOI: 10.3233/prm-201508
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the effects of whole-body vibration on individuals with cerebral palsy

Abstract: The purpose of this review is to examine how whole-body vibration can be used as a tool in therapy to help improve common physical weaknesses in balance, bone density, gait, spasticity, and strength experienced by individuals with cerebral palsy. Cerebral palsy is the most common movement disorder in children, and whole-body vibration is quickly becoming a potential therapeutic tool with some advantages compared to traditional therapies for individuals with movement disorders. The advantages of whole-body vibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 154 publications
0
3
0
Order By: Relevance
“…Maghbouli et al reported that CWBV training using a vibration frequency higher than 100 Hz may improve muscle strength and open-eye mediolateral postural control, recommending this technique as a promising approach for decreasing fall risk (58). Additionally, several recent studies found this modality to be an effective stimulus to improve neuromuscular performance and balance in healthy individuals (26), as well as in elderly individuals with neurological disorders (27,32).…”
Section: Discussionmentioning
confidence: 99%
“…Maghbouli et al reported that CWBV training using a vibration frequency higher than 100 Hz may improve muscle strength and open-eye mediolateral postural control, recommending this technique as a promising approach for decreasing fall risk (58). Additionally, several recent studies found this modality to be an effective stimulus to improve neuromuscular performance and balance in healthy individuals (26), as well as in elderly individuals with neurological disorders (27,32).…”
Section: Discussionmentioning
confidence: 99%
“…The WBV device is particularly helpful in individuals who are immobilized due to chronic health issues or have prolonged injuries, as typically seen in special needs, aging [22], overweight, and obese populations, as it is considered to be passive training, involving minimal risk of injury [23]. Prior research using WBV interventions have shown improvements in cardiovascular health [17,24], arthritis [25], flexibility [26], muscle soreness/stiffness [26], muscle strength/power [27], motor function and balance [28], and bone density [29] within mixed populations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, whole-body vibration (WBV) has been used as an alternative therapeutic exercise in a wide variety of rehabilitations, such as stroke [ 3 ], Parkinson’s disease [ 4 ], older adults [ 5 ], and CP [ 6 ]. Thus, WBV has become more popular in rehabilitation settings.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has focused on the role of various parameters of whole-body vibration training for children with spastic cerebral palsy—such as adjusting the vibration frequency and varying the time per session and duration—and other parameters, such as amplitude and wave direction, are usually fixed. In such WBV training, the frequencies were 25–40 Hz (6 min/s, 8 weeks) [ 6 ], 12–18 Hz (9 min/s, 3 months) [ 9 ], 12–18 Hz (9 min/s, 12 weeks) [ 10 ], 20 Hz (6 min/s, 6 weeks) [ 11 ], 5–25 Hz (18 min/s, 8 weeks) [ 13 ], and 13–18 Hz (12 min/s, 6 months) [ 14 ]. Previous studies found improvements in spasticity [ 6 , 10 , 11 ], muscle strength [ 10 , 11 ], gait ability [ 10 , 13 , 14 ], and GMFM88 [ 10 ], but no change in walking balance [ 10 ] or bone [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation